A real options model to assess the role of flexibility in forestry and agroforestry adoption and disadoption in the Lower Mississippi Alluvial Valley. (21st November 2012) - Frey, Gregory E.; Mercer, D. Evan; Cubbage, Frederick W.; Abt, Robert C.
Abstract Efforts to restore the Lower Mississippi Alluvial Valley's forests have not achieved desired levels of ecosystem services production. We examined how the variability of returns and the flexibility to change or postpone decisions (option value) affects the economic potential of forestry and agroforestry systems to keep private land in production while still providing ecosystem services. A real options analysis examined the impact of flexibility in decision making under agriculture, forestry, and agroforestry and demonstrated that adoption of forestry or agroforestry systems is less feasible than would be predicted by deterministic capital budgeting models.